(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2023)
The role of trade entrepreneurship in our time is considered in the article. The most famous representatives of trade entrepreneurship are identified. The development of trade entrepreneurship in Ukraine before the beginning of the full-scale invasion of Russia into Ukraine is studied. The main trends in the development of trade entrepreneurship in the world are shown. These trends are driven by three key factors: the growing role of online, value for money, and changing consumer lifestyles. Factors influencing changes in trade entrepreneurship during the war have been identified. It was noted that the closure or destruction of shops and warehouses in the areas of hostilities, the loss of control over objects in the occupied territories led to the losses of merchants and traders already exceeding 50 billion hryvnias. This, in particular, takes into account the losses of only the largest network companies. Therefore, the real number of direct losses will be much higher." Proposed ways to overcome negative phenomena in trade entrepreneurship caused by military aggression Examples of the activity of trading companies are described according to such criteria as the state of the trade network, prices, assortment, logistics, buyers, personnel, social component, etc. It was concluded that despite the significant losses of retail trade as a result of the destruction of the trade network and the disruption of supply chains, a tendency to improve the situation has already emerged, thus confirming the resilience of trade entrepreneurship to extreme conditions of existence, among which military aggression is the most difficult. In particular, state-owned companies helped Ukrainian retail to develop new supply chains. Sellers are trying to diversify supplies, looking for alternatives to scarce goods among imports and new producers in Ukraine There is an expansion of stores in the "around the house" format.